2007
DOI: 10.1080/13682820600939028
|View full text |Cite
|
Sign up to set email alerts
|

Long‐ and short‐term results of children's and adolescents' therapy courses for stuttering

Abstract: The implication is that intensive therapy courses can be helpful to some participants who stutter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…NIHR Journals Library www.journalslibrary.nihr.ac.uk 69 Koushik et al 2011, 121 Laiho and Klippi 2007, 70 Lattermann et al 2008, 26 Lincoln et al 1996, 77 Lincoln and Onslow 1997, 122 Mallard 1998, 79 O'Brian et al 2013, 86 Onslow et al …”
Section: Results Of the Effectiveness Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…NIHR Journals Library www.journalslibrary.nihr.ac.uk 69 Koushik et al 2011, 121 Laiho and Klippi 2007, 70 Lattermann et al 2008, 26 Lincoln et al 1996, 77 Lincoln and Onslow 1997, 122 Mallard 1998, 79 O'Brian et al 2013, 86 Onslow et al …”
Section: Results Of the Effectiveness Reviewmentioning
confidence: 99%
“…, 18 Franklin et al 2008 (quasi-RCT), 19 Hancock and Craig 1998 (quasi-RCT), 20 Hancock et al 1998 (quasi-RCT), 21 Harris et al 2002 (quasi-RCT), 22 Hewat et al 2006 (quasi-RCT), 23 Jones et al 2005, 24 Jones et al 2008, 25 Lattermann et al 2008, 26 Lewis et al 2008, 27 Menzies et al 2008, 28 Onslow et al 1994 29 (controlled before and after) Before and after (reported pre-intervention and post-intervention data with no comparator group) (86) Amster and Klein 2007, 30 Andrews et al 65 Kaya and Alladin 2012, 66 Kaya 2011, 67 Kingston et al 2003, 68 Koushik et al 2009, 69 Laiho and Klippi 2007, 70 Langevin and Boberg 1993, 71 Langevin and Boberg 1996, 72 Langevin et al 2006, 73 Langevin et al 2010, 74 Lawson et al 1993, 75 Leahy and Collins 1991, 76 Lincoln et al 1996, 77 Lutz 2009, 78 Mallard 1998, 79 Millard et al 87 Onslow et al 1990, 88 Onslow et al 1992, 89 Onslow et al 1996, 90 Pape-Neumann 2004, 91 Pollard et al 2009, 92 Reddy et al 2010, 93 Riley and Ingham 2000, 94 Rosenberger et al Cross-sectional (data from a single time point only) (11) Allen 2011, …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The final papers in this group (Andrews et al 2012, Trajkovski et al 2011) examined interventions for preschool and school aged children termed Syllable Timed et al, 2012 Before and after Lower Australia Adults, N = 20 Berkowitz et al, 1994 Before and after Higher USA School age, N = 8 Blomgren et al, 2005 Before and after Lower USA Adults, N = 19 Boberg and Kully, 1994 Before and after Higher USA Adolescents and adults, N = 49 Huinck et al, 2006 Before and after Lower Netherlands Adults, N = 25 Irani et al, 2012 Mixed method Higher USA Adults, N = 7 Laiho and Klippi, 2007 Before and after Higher Finland School age, N = 21 Langevin and Boberg, 1993 Before and after Higher Canada Adults, N = 10 Langevin and Boberg, 1996 Before and after Lower Canada Adults, N = 4 Langevin et al, 2006 Before and after Lower Canada and Netherlands Adults, N = 25 Langevin et al, 2010 Before and after Lower Canada Adults, N = 17 Lawson et al, 1993 Before and after Higher UK Adolescents, N = 15 and 19 Nilsen and Ramberg, 1999 Before and after Higher Sweden Adolescents, N = 13 Rosenberger, 2007 Before and after Higher Germany School-age children and adolescents, N = 19 and 15 Smits- Bandstra and Yovetitch, 2003 Before and after Higher Canada School age, N = 3 Stewart, 1996 Before and after Higher UK Adults, N = 12 Ward, 1992 Before and after Higher UK Unclear, N = 4 Speech (STS), and reported mean stuttering reductions of 96%SS (6%SS to 0.2%SS) at 12 months follow-up (ES = 1.8), and 14.4%SS to 6.7% (ES = 0.7). Data on self-reported severity, situation avoidance and quality of life confirmed these positive outcomes, however the authors noted considerable individual variation in response to the intervention.…”
Section: Speech Motor Interventionsmentioning
confidence: 99%
“…Studies that have reported on adolescent participants typically either have small participant numbers (Bray & Kehle, 1996;Hearne, Packman, Onslow, & O'Brian, 2008;Hewat, Onslow, Packman, & O'Brian, 2006) or have combined adolescent data with those from school-aged or adult clients, making interpretation of the results difficult (Antipova, Purdy, Blakeley, & Williams, 2008;Craig et al, 1996;Cream et al, 2010;Euler, Von Gudenberg, Jung, & Neumann, 2009;Laiho & Klippi, 2007;Langevin & Boberg, 1993).…”
Section: Treatment For Adolescents Who Stuttermentioning
confidence: 99%